2021
DOI: 10.1111/mec.15873
|View full text |Cite
|
Sign up to set email alerts
|

Whole genomes reveal multiple candidate genes and pathways involved in the immune response of dolphins to a highly infectious virus

Abstract: Wildlife species are challenged by various infectious diseases that act as important demographic drivers of populations and have become a great conservation concern particularly under growing environmental changes. The new era of whole genome sequencing provides new opportunities and avenues to explore the role of genetic variants in the plasticity of immune responses, particularly in non-model systems.Cetacean morbillivirus (CeMV) has emerged as a major viral threat to cetacean populations worldwide, contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…The basic GWAS is a commonly used approach that compares allele frequencies between case and control phenotypes and is used to identify loci associated with the trait of interest (Korte & Farlow, 2013); in this study we used both a chi-squared test and Fisher's exact test to reduce the chance of false positives whilst maintaining the greatest number of candidate SNPs possible. Our GWAS was complemented with Weir and Cockerham's F ST test (Weir & Cockerham, 1984) using the -weir-fst-pop tool in vcftools version 0.1.14 (Danecek et al, 2011) and SNPs with an F ST more than 5 SD from the mean were said to be significant SNPs (Axelsson et al, 2013;Batley et al, 2021; Figure S2). We used Weir and Cockerham's F ST to identify regions of genetic differentiation between our resolvers and nonresolvers.…”
Section: Identifying Candidate Snpsmentioning
confidence: 99%
“…The basic GWAS is a commonly used approach that compares allele frequencies between case and control phenotypes and is used to identify loci associated with the trait of interest (Korte & Farlow, 2013); in this study we used both a chi-squared test and Fisher's exact test to reduce the chance of false positives whilst maintaining the greatest number of candidate SNPs possible. Our GWAS was complemented with Weir and Cockerham's F ST test (Weir & Cockerham, 1984) using the -weir-fst-pop tool in vcftools version 0.1.14 (Danecek et al, 2011) and SNPs with an F ST more than 5 SD from the mean were said to be significant SNPs (Axelsson et al, 2013;Batley et al, 2021; Figure S2). We used Weir and Cockerham's F ST to identify regions of genetic differentiation between our resolvers and nonresolvers.…”
Section: Identifying Candidate Snpsmentioning
confidence: 99%
“…In this respect, genome-wide comparative analysis of the Indo-Pacific bottlenose dolphin (Tursiops aduncus) Australian population hit by a CeMV outbreak in 2013 revealed that single nucleotide polymorphisms (SNPs) among survivor and nonsurvivor dolphins mapped to genes involved in innate and adaptive immune response, as well as in cytokine signaling pathways. 37,38 Likewise, recent full-length RNA sequencing of the Sperm whale (Physeter macrocephalus) skin transcriptome led to the identification of gene products with essential functions in the antiviral innate immune response, including nucleotide-binding oligomerization domain-containing protein 1 (NOD1), NOD2 and nuclear factor kappa B (NF-kB) proteins. 39 Furthermore, at the population and individual levels within a single species, the immune status can be influenced by both intrinsic factors such as given physiological conditions (e.g.…”
Section: Priority 3: Molecular Basis For Different Host Susceptibility To Cemv Infectionmentioning
confidence: 99%
“…Nonetheless, different responses to CeMV infection can be ascribed, at the species level, to genetic features leading to resistance or susceptibility to CeMV within geographically isolated populations. In this respect, genome‐wide comparative analysis of the Indo‐Pacific bottlenose dolphin ( Tursiops aduncus ) Australian population hit by a CeMV outbreak in 2013 revealed that single nucleotide polymorphisms (SNPs) among survivor and nonsurvivor dolphins mapped to genes involved in innate and adaptive immune response, as well as in cytokine signaling pathways 37,38 . Likewise, recent full‐length RNA sequencing of the Sperm whale ( Physeter macrocephalus ) skin transcriptome led to the identification of gene products with essential functions in the antiviral innate immune response, including nucleotide‐binding oligomerization domain‐containing protein 1 (NOD1), NOD2 and nuclear factor kappa B (NF‐kB) proteins 39 .…”
Section: Priority 3: Molecular Basis For Different Host Susceptibilit...mentioning
confidence: 99%
“…( McKeena et al, 2010), with functions RealignerTargetCreator and IndelRealigner used with default settings to ensure indels were parsimoniously represented and to reduce potential false variants. The SNP data set was identified by calling SNPs from the reference genome alignment using BCFtools v1.19 (Danecek et al, 2016), and then filtered using VCFtools v0.1.15 (Danecek et al, 2011) similar to the approach of Batley et al (2021). To reduce the calling of false SNPs due to artefacts of the ddRAD-seq approach (i.e., multicopy loci, paralogs, sequencing errors) several filtering steps were applied.…”
Section: Bioinformatics Of the Genomic Data Setmentioning
confidence: 99%